Negative affect provides a context for increased distrust in the daily lives of individuals with a history of childhood maltreatment$research article - Schmitz, Sara Elena; Niedtfeld, Inga; Lane, Sean P.; Seitz, Katja I.; Hepp, Johanna (Journal of traumatic stress, 2023)
Evidence on individuals affected by posttraumatic stress disorder (PTSD) following childhood maltreatment (CM) supports cognitive models suggesting that trauma engenders distrust and interpersonal threat sensitivity. We examined the associations between CM and both distrust and interpersonal threat sensitivity in daily life and investigated whether momentary negative affect (NA) provides a context that strengthens this association. Hypotheses were based on cognitive models of trauma and the feelings-as-information theory. In a 7-day ambulatory assessment study with six semirandom daily prompts (2,295 total), we measured self-reported momentary NA and assessed behavioral trust as well as interpersonal threat sensitivity via facial emotion ratings with two novel experimental paradigms in 61 participants with varying levels of CM (45,900 total trials). As hypothesized, NA was associated with increased momentary distrust, β = .03, p = .002, and interpersonal threat sensitivity, β = −.01, p = .021. Higher levels of CM were associated with more negative emotion ratings, independent of affective context, β = −.07, p = .003. Momentary behavioral distrust was associated with CM at high levels of momentary NA, β = .02, p = .027. The findings for both tasks support the feelings-as-information theory and suggest that cognitive alterations surrounding distrust and interpersonal threat, which were originally proposed for PTSD, likely also affect individuals with a history of CM.